O ESTABELECIMENTO DA EDUCAÇÃO ESCOLAR EM TEMPO INTEGRAL NOS MUNICÍPIOS DA REGIÃO METROPOLITANA DA GRANDE VITÓRIA/ES (2015-2019) - Gomes, Deborah Gomes Moura (2020)
This research integrates the research line called " Teaching and Educational Process Management", Graduation Program of Professional Master's in Education, of the Federal University of Espirito Santo, it is also included to the Management, Work, and Educa